The Original Meanings of the Social Sciences as a Foundation for Illustrating a Renewed Reflection on their Current Situation and Future Challenges (London Journal of Research In Humanities and Social Sciences, 2025)
The mere act of attempting to say something about the social sciencestheir origin, history, development, and destinyis, in itself, an ambitious and excessive endeavor. Who could even produce a state of the art of any of the disciplines or subdisciplines that today fall under that broad label? To say something meaningful in this regard, we would have to rely on the enormous collective efforts that some groups of scholars and certain institutions have undertaken in recent years (Wallerstein, I., 2006; Heilbron, J.; L. Magnusson & B. Wittrock, 1998; Porter, T. and D. Ross, 2003; UNESCO, 2010; UNESCO, 2013).
Keywords: educational inclusion; premature baby; child development; learning difficulty